PERAN APLIKASI KOMPUTER BERBASIS AKUNTANSI UNTUK BADAN USAHA DALAM PERSFEKTIF SISTEM INFORMASI - Rahmawati, Mari (www.bsi.ac.id, 2015)
ABSTRACT Today, the use of computers in all fields of human facilitate work in data processing since the previous manual system to a computerized system to improve the ability of computer machine and human resources more efficiently and better. The development of technology requires an information system that is fast and precise. The need for information followed by data collection and processing are effective and efficient. Accounting information is the most important part of all the information required by the management of a company. Accounting information used as a basis for determining the financial policy of the company against the performance results and financial condition of the company. In this day and age it's time to apply the accounting application that can assist and facilitate the process of preparation of financial statements, when compared to the manual process is cumbersome and requires a long time. In addition, the use of accounting applications to minimize errors that can occur in the form of transaction recording error caused by human error. We have had many emerging applications that facilitate the work of accounting for our users and users of accounting information. As for the types of applications include the following accounting Zahir Accounting, MYOB Accounting, Accurate and others.Keywords: Accounting , Information Systems , Computer Applications .